Cannabinoid receptor 2: a potential novel therapeutic target for sepsis?. Issue 2 (4th March 2019) - He, Qianwen; Xiao, Fei; Yuan, Qinghong; Zhang, Jingjing; Zhan, Jia; Zhang, Zongze
Abstract: Objective: Sepsis is life-threatening organ dysfunction caused by a dysregulated host response to infection. It is the most common cause of death among critically ill patients in non-coronary intensive care units and the incidence continues to rise. Although advanced management was applied, the prognosis of sepsis patients remains poor. As a G-protein coupled receptor, cannabinoid receptor 2 (CB2R) was implicated in a wide variety of diseases. In this study, we aimed to investigate the role of CB2R in sepsis. Methods: Literature search was performed using "sepsis" and "Cannabinoid Receptor" as search terms in PubMed, EMbase, and the Cochrane Library. Results and Discussion: Briefly, 97 records were identified by the search strategy, of which 76 were duplicate or irrelevant publications. With the anti-inflammatory and immunomodulatory effects, CB2R is a novel and promising therapeutic target in the management of sepsis. Indeed, specific CB2R agonists have been reported to attenuate leukocyte recruitment, oxidative burst, systemic inflammatory mediator release, bacteremia, and lung tissue damage, while improving survival in different sepsis models. In addition, autophagy has also been implicated in the protective role of CB2R activation in sepsis. However, almost all of the current outcomes result from animal studies or in vitro cultured cells. Due to the lack of clinical evidence and the ambiguous mechanisms underlying, the clinical application of CB2R stimulation in sepsis is limited. Further studies are needed to delineate the therapeutic effect and the related-pathways of CB2R agonists in sepsis.